Elemental Status of Pregnant and Lactating Women in Bassa L.G.A of Plateau State, Nigeria - Madukosiri, C.H.; Adoga, G.I. (Pakistan Journal of Nutrition, 2011)
The present study has determined the serum levels of ten elements (sodium, potassium, magnesium, calcium, zinc, copper, iron, manganese, phosphorus and chloride) in the three trimesters of pregnancy and in lactation. Four hundred and thirty two apparently healthy pregnant, lactating and non-pregnant/non-lactating (control) women participated in the study. Atomic absorption spectrophotometric method was used for the analysis of some of the elements. The determination of inorganic phosphate was carried out by phosphomolybdic acid method, while the level of chloride was measured by the mercuric nitrate method. Our results showed that the serum sodium levels in pregnancy were significantly higher than the levels obtained in their control counterpart and in lactation (p<0.05). In the same vein, the levels of calcium determine from the pregnant groups were higher than that from the lactating group (p<0.05). On the other hand the level of zinc in the lactating group was higher than those in the rest groups (p<0.05). The estimated levels of iron (in all the groups) were within the literature range and there was no significant difference between them (p<0.05). This study has established the normal levels of ten serum elements in pregnancy and lactation for indigenes of Bassa L.G.A of Plateau state. Base-line nutritional status of this sort is helpful in guarding against mineral deficiency/overload in the course of management of antenatal and postnatal women in Bassa areas.